Zipporah, Queen of the Desert: Living as Queer and Trans Jews in Australia - Rosenberg, Shoshana (Curtin University, 2022)
This thesis explores the lived experiences of queer and trans Jewish people in so-called Australia. It focuses the ways queer and trans Jews may experience multiple marginalisations, as well as areas where the meeting of these lived experiences produces unique knowledges and perspectives. Through a bricolage of autoethnography, interviews, and analysis of literature around the intersections of Jewishness, queerness, and transness, the thesis provides insight into the ways gender, sexuality, faith, and culture feed into each other.